2014
DOI: 10.21608/jpp.2014.64760
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF BIO-STIMULANT AND SOIL AMENDMENT ON VEGETATIVE GROWTH, YIELD AND FRUIT QUALITY OF Pyrus communis cv. 'LE CONTE' PEAR TREES.

Abstract: The experimental trial was consummated throughout two successive seasons (2012 and 2013) at a commercial orchard at El-Khatatba city, Monifia Governorate, Egypt. It intended to find out the possibility of enhancing "Le Conte" pear trees productivity under local condition in the newly reclaimed lands. Thus, the individual and combined applications of bio-stimulant (EM) and soil amendment (NPK humate) applied as soil drench fourteen times at 2 weeks intervals commencing from first February till mid August to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The use of organic products has received a lot of attention in the recent period, furthermore, this new system of agricultural production that contain Humic acid has become one of the most important organic compounds used in this field, if it is found that the addition of humic acid to soil leads to increase the cation exchange capacity of soil and increases its pH and thus increases the availability of nutrients and increases the growth of roots and their branches (7) . (8) found in their study on Anna cultivar apples that the addition of humic acid to soil by 30 cm 3 .tree -1 has led to significant increase in the number of leaves per branch -1 and the area of the leaf increased with an increase in yield by 25.6% in addition to an increase in the average weight of the fruit and the percentage of total soluble solids, (9) also obtained similar results when studying Annacultivar apple trees, and (10) stated an increase in tree yield, fruit count per tree, and average of fruit weight of pear (Leconte cultivar) when adding 100 ml per tree of humate-NPK combination (10% humate ratio) to the soil. (11) Had gained the same results on apricot trees (Canino cultivar).…”
Section: Introductionmentioning
confidence: 66%
“…The use of organic products has received a lot of attention in the recent period, furthermore, this new system of agricultural production that contain Humic acid has become one of the most important organic compounds used in this field, if it is found that the addition of humic acid to soil leads to increase the cation exchange capacity of soil and increases its pH and thus increases the availability of nutrients and increases the growth of roots and their branches (7) . (8) found in their study on Anna cultivar apples that the addition of humic acid to soil by 30 cm 3 .tree -1 has led to significant increase in the number of leaves per branch -1 and the area of the leaf increased with an increase in yield by 25.6% in addition to an increase in the average weight of the fruit and the percentage of total soluble solids, (9) also obtained similar results when studying Annacultivar apple trees, and (10) stated an increase in tree yield, fruit count per tree, and average of fruit weight of pear (Leconte cultivar) when adding 100 ml per tree of humate-NPK combination (10% humate ratio) to the soil. (11) Had gained the same results on apricot trees (Canino cultivar).…”
Section: Introductionmentioning
confidence: 66%
“…Attributable to its positive influence on the soil, compost amendment significantly alleviated the harmful effects of drought resulting in better growth and yield. Bio stimulants like EM, have a positive roles in sustaining the ecosystem (Farrag and Bakr, 2023), such as: Lactobacillus Rhodopseudomonas, and Saccharomyces (Shalan, 2014). They improved growth, yield and maturing of lettuce crop (Rashwan & El-Saied, 2022).…”
Section: Introductionmentioning
confidence: 99%